2014
DOI: 10.1590/s0100-39842014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between PET/CT results and histological and immunohistochemical findings in breast carcinomas

Abstract: ObjectiveTo correlate the results of 18F-fluoro-2-deoxy-D-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) performed with a specific protocol for assessment of breasts with histological/immunohistochemical findings in breast carcinoma patients.Materials and MethodsCross-sectional study with prospective data collection, where patients with biopsy-confirmed breast carcinomas were studied. The patients underwent PET/CT examination in prone position, with a specific protocol for assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
5
13
0
Order By: Relevance
“…In agreement with the foregoing, numerous studies in primary breast cancers have demonstrated statistically significant associations between higher values of maximum SUV and histological type (IDC), histological grade (III), tumor diameter, mitotic index, Ki-67 expression, nuclear atypia, hormone receptor (HR) negativity, high score of HER2 expression, lymph node metastasis all related to breast carcinomas' higher aggressiveness and more unfavorable prognosis ( Fig. 1) (Bitencourt et al, 2014;Lavayssière et al, 2009;Kitajima et al, 2015;Ueda et al, 2008). On the contrary, Shimoda et al showed a significant association between SUV values and mitotic counts, Ki-67, and nuclear grade, but not with tumor size, age, histology, HR expression and HER2 overexpression (Shimoda et al, 2007).…”
Section: Correlation Between 18 F-fdg Pet/ct Results and Breast Cancesupporting
confidence: 80%
“…In agreement with the foregoing, numerous studies in primary breast cancers have demonstrated statistically significant associations between higher values of maximum SUV and histological type (IDC), histological grade (III), tumor diameter, mitotic index, Ki-67 expression, nuclear atypia, hormone receptor (HR) negativity, high score of HER2 expression, lymph node metastasis all related to breast carcinomas' higher aggressiveness and more unfavorable prognosis ( Fig. 1) (Bitencourt et al, 2014;Lavayssière et al, 2009;Kitajima et al, 2015;Ueda et al, 2008). On the contrary, Shimoda et al showed a significant association between SUV values and mitotic counts, Ki-67, and nuclear grade, but not with tumor size, age, histology, HR expression and HER2 overexpression (Shimoda et al, 2007).…”
Section: Correlation Between 18 F-fdg Pet/ct Results and Breast Cancesupporting
confidence: 80%
“… 8 , 27 , 28 In addition, 18 F-FDG uptake is lower on tumors with positive hormone receptor expression (luminal A and luminal B subtypes), when compared with less-differentiated tumors with negative hormone receptor expression (Her-2 and triple-negative subtypes). 29 , 30 Several methods have been developed to improve the current results of PET-CT for the diagnosis of breast lesions. Recently, a research group has been developing a dedicated simultaneous PET-MRI breast imaging system, which allows a combination of a high-resolution PET scan with morphologic and functional MRI data in a single study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies were developed about imaging quality ( 10 , 11 ) , recommendations for breast cancer screening ( 12 ) , adherence to mammography ( 13 ) , new techniques related to breast cancer diagnosis ( 14 - 16 ) , as well as about the relevance of internal audits in mammography services as a tool to depict the service quality ( 17 ) .…”
Section: Introductionmentioning
confidence: 99%